Real time ultrasound assessment of contact progress between food gels and tongue mimicking surfaces during a compression. (December 2020) - Mantelet, Mathieu; Srivastava, Rohit; Restagno, Frédéric; Souchon, Isabelle; Mathieu, Vincent
Abstract: An in vitro study was conducted to further explore the potential of an emerging ultrasound method for monitoring in real time the progress of the contact between gels with different physical properties and tongue mimicking surfaces (TMSs) during uniaxial compressions. A 1-MHz ultrasound transducer was used to measure the apparent reflection coefficient ( R* ) of the interface between TMSs (of varied roughness) and gels (agar and/or gelatin). The patterns of R* variations clearly depended on the gels capacity to deform and mold the asperities of the TMSs during compression. Rough TMSs induced a significant decline of R* values, demonstrating an increase of the fraction of the TMSs in direct contact with the gels. Rigidity, fracture properties or adhesion energy of gels influenced the kinetics of contact progress and associated patterns of R* variations. Moreover, the presence of a thick lubrication film between the gels and the TMSs promoted the transmission of ultrasound waves (acting as a coupling agent) and led to decreasing values of R* . Such phenomena were observed both when depositing a water lubrication film of controlled thickness on the TMSs (to mimic salivary film) and when considering gels with high water release capacities. The study confirms the potential of ultrasound methods for exploring physical phenomena related to interactions between food and tongue surface. Such developments could better contribute to unravel the determinants of texture perceptions during food oral processing. Graphical abstract: Image 1 Highlights: Ultrasound showed gels capacity to deform and mold tongue surface asperities. The contact between gels and tongue mimicking surfaces varied with gel properties. Effect of lubrication at tongue food interface was also detectable with ultrasound. The method could help to better interpret the determinants of texture perceptions.